(untitled) (Asian Journal of Pharmaceutics (AJP), 2018)
Context: Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality. Aims: This paper presents a study that was conducted to assess the socioeconomic effects of a CAP episode to help policymakers to create effective prevention and control measures. Settings and Design: This study used an incidence-based approach from a societal perspective. Materials and Methods: The sample comprised 255 hospitalized patients at the Respiratory Department at Trung Vuong General Hospital during a 12-week period in 2017. Payment data were also collected. Results: Overall, there were 148 (58.0%) men and 107 (42.0%) female with a mean age of 66 Â± 16 years. More than half 158 (62.0%) were older than 65. The current study showed the mean treatment cost to be approximately 629 for CAP inpatients; this included direct and indirect costs. The average informal cost of treating one CAP patient was estimated at 297. On average, the biggest expenses were those related to direct medical costs - 76.6% (481). The mean CAP-related direct non-medical and indirect costs accounted for 19.3% and 4.1%, valued at 121 and 26, respectively. The results of the study also showed a significant relationship between length of stay and average cost of treatment per CAP episode. Conclusions: The results of this study can be used to improve the allocation of resources for CAP control in Vietnam and to provide a foundation for future analyses of the cost-effectiveness of pneumococcal vaccines or other methods for controlling CAP.